(untitled) (Development Service Industry Management, 2025)
The article explores the organizational and technological factors influencing the implementation of Agile methodologies in a large international IT company during the period from 2013 to 2025. The analysis encompasses the initial stages of formal adoption—characterized by managerial errors, low team motivation, and lack of a consistent strategy—as well as the gradual transformation towards an effective agile management model with high levels of adaptability and productivity. The aim of the study is to identify correlations between leadership practices, team motivation, technological infrastructure (particularly the implementation of a low-code platform), and the effectiveness of Agile approaches. The methodology is based on systemic analysis, visualization of velocity and CSAT metrics, and modeling of productivity dependencies on leadership styles. The results demonstrate that the transition from formal to effective Agile practices was driven by adaptive leadership, strategic clarity, and robust feedback loops. The development of a low-code platform also had a synergistic effect by enhancing the quality of digital products, even in times of organizational crisis. The scientific novelty lies in the comprehensive integration of qualitative and quantitative methods for analyzing transformation processes in IT organizations. The practical significance of the findings includes the potential application of the proposed approaches to build resilient and efficient management models in dynamic digital environments. The conclusions may be adapted to assess organizational agility maturity, design transformation programs in IT companies, and develop educational curricula for digital project leaders. This case study highlights the value of long-term empirical observation of change, enabling practice-oriented conclusions with strong applicability in innovation management, digital transformation, and corporate leadership